`AYYAPPAN SARANAM':1 MASCULINITY AND THE SABARIMALA PILGRIMAGE IN KERALA - Filippo Osella & Caroline Osella (J. Roy. anthrop. Inst. (N.S.) 9, 729-754, 2003)
Sabarimala - a South Indian all-male pilgrimage to Ayyappan, a hyper-male deity born from two male gods - plays a role in constructing male identities, at both external (socialstructural) and internal (psychological) levels. The pilgrimage draws creatively on relationships between two South Asian male figures: renouncer and householder, breaking down the opposition between transcendence and immanence to bring into everyday life a sense of transcendence specific to men. This also has masculine and heroic overtones, characterized by ascetic self-denial and pain and by the identification of pilgrims with the deity and his perilous mountain-forest journey. Pilgrimage bestows power as blessings from Ayyappan and as specifically masculine forms of spiritual, moral, and bodily strength, while acting as signifier of masculine superior purity and strength and of male responsibilities towards family welfare. Sabarimala merges individual men both with the hyper-masculine deity and with a wider community of men: other male pilgrims, senior male gurus (teachers). This merger is both social and personal. A normal and universal sense of masculine ambivalence and self-doubt has a specific local-cultural resolution, when boys and men experience strengthening of the gendered ego through renunciatory self-immersion in a `greater masculine'. The ostensibly egalitarian devotional community is actually hierarchical: pilgrims surrender themselves to deity and guru, while equality and friendship between men can be celebrated and performed precisely because it is predicated upon a deeper sense of difference and hierarchy - gender - with woman as the absent and inferiorized other. Such segregated celebrations of masculinity work both towards masculinity's reproduction - through processes of `remasculinization' - and in the limiting of masculinity to males.